EXPLORING PSYCHIC AND BODILY TRAUMA IN KASHMIRI ANGLOPHONE LITERATURE: AN ANALYSIS OF SIDDHARTHA GIGOO’S The GARDEN OF SOLITUDE AND NAYEEMA MAHJOOR’S LOST IN TERROR - Lahkar, Barasha; Swami, Indu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Cursed by the long years of armed militancy and the counter insurgency measures taken to ensure India’s national security, Kashmir has almost turned to a dystopian land. Writers have responded to this aspect of the history of this region by producing works that record and commemorate particular events and experiences which changed the lives of people altogether. Of particular significance in these works is the documentation of the impact of the violence on the everyday lives of people, many of whom though unaware of or unrelated to the main issues being debated, are affected beyond measure by the turn of the events. Invoking the memories of the turbulent period of history which damaged their lives irreparably, the writers from Kashmir have created of a significant corpus of literature that represents the damages done to the body and psyche of the people living there. This paper endeavours to foreground the exploration of trauma in Kashmiri Anglophone literature through a reading of Siddhartha Gigoo’s The Garden of Solitude (2011) and Nayeema Mahjoor’s Lost in Terror (2016). It seeks to see how literature performs the task of portraying the unspeakable and unpresentable to the readers by blending history, fiction and memory together.